Analisis Regresi Cox Proportional Hazard Untuk Menentukan Faktor-Faktor yang Memengaruhi Lama Studi Mahasiswa - Arpen, Inti; Lesnu, Yopi Andry; Wattimena, A. Z.; Matdoan, M. Yahya (Jurnal Matematika; Vol 11 No 1 (2021), 2021)
Higher education has an important role for students, so that students can pursue their studies and can complete their studies on time. Length of study is the time it takes a student to complete his studies. For undergraduate level (S1) is 4 years and no later than 7 years. There are several factors that influence the length of study of students, namely internal factors and student external factors. The survival analysis method is a statistical method that studies the duration of an event or event that occurs. The Cox regression model is a well-known model in survival analysis for explaining the relationship between individual failure at a time and explanatory variables in the presence of censorship. The results of this study indicate that the factors that influence the length of study of students are the factor of GPA> 3, factors majoring in mathematics, majoring in biology and factors majoring in physics.